Excision Dominates Pseudogenization During Fractionation After Whole Genome Duplication and in Gene Loss After Speciation in Plants - Yu, Zhe; Zheng, Chunfang; Albert, Victor A.; Sankoff, David (Frontiers in Genetics, 2020)
We take advantage of synteny blocks, the analytical construct enabled at the evolutionary moment of speciation or polyploidization, to follow the independent loss of duplicate genes in two sister species or the loss through fractionation of syntenic paralogs in a doubled genome. By examining how much sequence remains after a contiguous series of genes is deleted, we find that this residue remains at a constant low level independent of how many genes are lost -- there are few if any relics of the missing sequence. Pseudogenes are rare or extremely transient in this context. The potential exceptions lie exclusively with a few examples of speciation, where the synteny blocks in some larger genomes tolerate degenerate sequence during genomic divergence of two species, but not after whole genome doubling in the same species where fractionation pressure eliminates virtually all non-coding sequence.